International Encyclopedia of Gambling. - THOMPSON, WILLIAM N. (ABC-CLIO, 2009)
The International Encyclopedia of Gambling seeks to explain the gambling phenomenon through an in-depth exploration of gambling operations around the world. More than 300 entries reflect the global stretch of the industry as they examine games, venues, players and other leading figures, legal issues, the history of gaming, and the literature on the subject.